Peripheral osteoma in a young patient: A marker for precancerous condition? - P Singhal; A Singhal; R Ram; R Gupta (Wolters Kluwer Medknow Publications, 2012)
Osteoma is a benign osteogenic tumor arising from the proliferation of cancellous or compact bone. The osteoma can be central, peripheral, or of an extraskeletal type. Peripheral type of osteoma is most common in the lower jaws, which occurs at the surface of the cortical bone and is sessile or pedicled. The overall incidence of osteoma is low, affecting 0.01-0.04% of the population; osteomas comprise 12.1% of benign bone tumors and 2.9% of all bone tumors. Most of the osteomas occurring in the mandible are dense osteomas, and the cancellous osteoma is comparatively rare. Maxillofacial osteoma associated with cutaneous sebaceous cysts, multiple supernumerary teeth, and colorectal polyposis is known as Gardener's syndrome. However, in some cases, maxillofacial osteomas with multiple impacted and supernumerary teeth are not accompanied by a fixed complex of symptoms. We report one such case in a 15-year-old female patient.